PEMODELAN MATEMATIKA UNTUK NETWORKING DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA TABUNGAN DEPOSITO MUDHARABAH: Studi Kasus Bank Syariah Indonesia KCP Sumenep Trunojoyo 1 - Wardatus Syarifah; Zaitunah Zaitunah (LPPM Universitas Bina Bangsa, 2023)
Networking is a method that can be used to optimize the planning and network of a manager to schedule and supervise work activities. By achieving a high level of customer satisfaction and can prevent customer turnover. Regression analysis is a statistical process for estimating the relationship between variables, namely in the form of modeling techniques and analyzing several variables on the basis of the form of the relationship between one dependent variable and one or more independent variable. The purpose of this study is to obtain a mathematical model of the purpose of this study is to obtain a mathematical model of networking and service quality on customer satisfaction and to find out what factors have the most influence on networking and service quality on customer satisfaction. The results of calculations using regression analysis obtained a mathematical model of networking and service quality on customer satisfaction, namely Y = 28,987 + 0.403(X1) + 0.155 (X2). With a significant level of all positive variables 0.000 <0.05